THE IMPLEMENTATION OF MARKETING STRATEGY ON DISTRIBUTOR COMPANY (CASE STUDY AT PT HANNA INSTRUMENTS INDOTAMA) - Azhar Azzura Bachtiar; Purwanto - (Journal of Management and Leadership, 2021)
This research purposes to describe the implementation of 7P’s marketing strategy at PT Hanna Instruments Indotama towards purchase decision. In this research using some indicators which one is like product, price, place, promotion, people, process, and physical evidence. To collecting the data there are 97 respondents who are using Hanna Instruments product through questionnaire at several industries located in Bandung. The research method applied a quantitative method with descriptive approach using Statistical Package for the Social Sciences (SPSS) analysis. The consequences of this research show that price, promotion and place has no influence to purchase decision. It can conclude 4 out of 7 hypotheses show a significant influence on purchase decision. The influence of product, people, process, physical evidence. The implementation of 7P’s as marketing strategy toward purchase decision accounts for 61.9% and the other 38.1% is account for another factor that does not discussed.